Downsizing in Organizations: The Return to Basics - Valencia-Pinzón, Manuel Arturo; Henao-Rosero, Andrés (Universidad Pontificia Bolivariana, 2020)
This article is a reflection on the balance that exists between trends and administrative processes, the reduction of personnel, and restructuring in organizations; for what is investigated among the most representative and cited articles, using databases such as Scopus and Web of Science; In addition to having taken into account, some important authors have been published and published on this subject. Nowadays, there are many systems of work in methodologies, models and theories that expose ideas and techniques with the intention of making strategic strategies and improvements in the organization with the purpose of achieving greater profitability or competitiveness in the market, but sometimes implementation of something new and novel, is not the most successful solution for an area or organization. In summary, the existing models and techniques in the administration can not be the only solution to the requirements of an area or organization; Therefore, reduction is an increasingly innovative practice on the part of the directors and managers of the 21st century; Therefore, downsizing is a key and important aspect for the development of organizations and their administration.